Pressure and help seeking for alcohol problems: Trends and correlates from 1984 to 2005 - Korcha, Rachael A. (2012)
BACKGROUND: Individuals with alcohol problems frequently report receipt of pressure from a variety of formal and informal sources. While some studies have shown a positive association between receipt of pressure and treatment seeking, other studies have not found a clear association. The mix of findings may be due to several study design factors including sample limitations, lack of contextual alcohol measures as moderators, and failure to include assessment of internal beliefs that relate to help seeking. METHODS: Current drinkers from the National Alcohol Surveys (NAS) from 1984-2005 (N=16,183) were used to describe the association between pressure and help seeking using moderators that included frequent heavy drinking, alcohol related negative consequences, and beliefs about abstention or moderation of alcohol consumption. RESULTS: The rate of help seeking in the past year was 1.6% across all NAS surveys with Alcoholics Anonymous being the predominant source of help sought followed by physical or mental health services. In 1984 and 1990 approximately 80% of those seeking help also received pressure. The percent declined to 57% in 1995 and leveled off at 64% in 2000 and 61% in 2005. Logistic regression models showed an association between past year receipt of pressure and help seeking. Frequent heavy drinking, alcohol related negative consequences, and strong beliefs about alcohol use were also associated with help seeking, however, they did not moderate the relationship between pressure and help seeking. CONCLUSIONS: Pressure is associated with help seeking as are a variety of other factors, including heavy alcohol consumption, negative consequences, and strong beliefs about moderate alcohol use. However, the effect of these factors appears to be independent of pressure and not interactive. Future research needs to assess the types of pressure and impact on help seeking to inform public policy and treatment providers as to who receives what type of pressure, when it is helpful, and when it is counterproductive.